P.015 What Happens to the Worried Well? – Follow-up of Subjective Cognitive Impairment. (November 2021) - Sutherland, M; Kirk, A; Karunanayake, C; O'Connell, M; Morgan, D
Abstract : Background: Concern around perceived neurocognitive decline is increasing, leading to increased number of referrals and anxiety for patients. We aimed to explore the likelihood of the "worried well" experiencing neurocognitive decline. Methods: 166 "worried well" patients who attended the Rural and Remote Memory Clinic between 2004 and 2019 were included. Mini Mental Status Examination, Center for Epidemiologic Studies Depression Scale, and Functional Assessment Questionnaire scores were measured and compared at initial assessment and at 1-year follow-up. MMSE scores over time were assessed with a mean follow-up of 2.95 years (SD 2.87). Results: There was no statistically significant difference in MMSE, CESD, or FAQ scores between clinic day and one-year follow-up, and no consistent pattern of MMSE score over time. Of the 166 patients with SCI on initial assessment, nine were eventually given a neurological diagnosis. Conclusions: There is no pattern of neurologic decline observed in the "worried well". Though the likelihood of a patient with SCI developing a neurological diagnosis is reassuringly low, (9/166), it is not irrelevant. This, along with the benefits of early diagnosis and treatment for dementia, leads us to believe that patients with SCI should still be seen in follow-up at least at the one-year mark.